Analysis of Severe Acute Respiratory Syndrome 2 Replication in Explant Cultures of the Human Upper Respiratory Tract Reveals Broad Tissue Tropism of Wild-Type and B.1.1.7 Variant Viruses. (15th October 2021) - Schulze, Jessica; Mache, Christin; Balázs, Anita; Frey, Doris; Niemeyer, Daniela; Olze, Heidi; Dommerich, Steffen; Drosten, Christian; Hocke, Andreas C; Mall, Marcus A; Hippenstiel, Stefan; Wolff, Thorsten
Abstract: Background: The upper respiratory tract (URT) is the primary entry site for severe acute respiratory syndrome 2 (SARS-CoV-2) and other respiratory viruses, but its involvement in viral amplification and pathogenesis remains incompletely understood. Methods: In this study, we investigated primary nasal epithelial cultures, as well as vital explanted tissues, to scrutinize the tropism of wild-type SARS-CoV-2 and the recently emerged B.1.1.7 variant. Results: Our analyses revealed a widespread replication competence of SARS-CoV-2 in polarized nasal epithelium as well as in the examined URT and salivary gland tissues, which was also shared by the B.1.1.7 virus. Conclusions: In our analyses, we highlighted the active role of these anatomic sites in coronavirus disease 2019. Abstract : This communication reports widespread and similar replication competence of early SARS-CoV-2 and its B.1.1.7 variant in explanted tissues of the human upper respiratory tract and primary nasal epithelial cells. B.1.1.7 induced a reduced type III IFN response in nasal cells.